Improvement of brightness, color purity, and operational stability of electrochemiluminescence devices with diphenylanthracene derivatives. Issue 47 (24th November 2017) - Hwang, Heedong; Kim, Jin Kon; Moon, Hong Chul
Abstract : We synthesized a highly soluble ionophilic 9, 10-diphenylanthracene (I-DPA) by incorporating imidazolium groups into a DPA core. Abstract : We synthesized a highly soluble ionophilic 9, 10-diphenylanthracene (I-DPA) by incorporating imidazolium groups into a DPA core. With the prepared I-DPA as an electrochemiluminescence (ECL) luminophore, the resulting ECL device emitted blue light. In comparison with unmodified DPA, a well-known representative ECL blue emitter, the ECL device including I-DPA emitted brighter and purer blue light with improved operational stability. Due to excellent compatibility of the I-DPA with polyvinylacetate (gelator), we could successfully prepare homogeneous ECL gels, and fabricated flexible blue-emitting ECL devices on a plastic substrate.